201 A Re-audit of Lignocaine 5% Medicated Plaster (Versatis®) Prescribing in an Older Adult Inpatient Population Following Changes to Reimbursement Provisions. (16th September 2019) - McCartan, Deirdre; Poff, Alison; Lee, Stuart; Martin, Alan
Abstract: Background: Lignocaine 5% medicated plasters (Versatis®) are licensed only for treatment of postherpetic neuralgia. Our 2017 audit of Versatis® prescribing recorded a potential cost of €28, 297/year for just 26 patients, all off-label. We noted however the limited choice of analgesics in older adults due to co-morbid conditions such as CKD and frailty. The 2017 Medicines Management Programme (MMP) directive for label-only Versatis® prescribing aimed to reduce annual exchequer costs of €30 million noting 25, 000 people had prescriptions under Community Drugs Schemes (CDS) in 2016. Methods: We conducted a re-audit of Versatis® prescribing on five core geriatric medical, orthogeriatric and rehabilitation wards across three inpatient sites. Indication for, duration of and patient's personal view of the plaster was recorded. Pharmacy provided medications costings. Cost per day and per length of stay were calculated. All other prescribed analgesics were recorded. Results: Analgesics prescribed for 127 patients were recorded. Mean age was 81 years, 63% female. 4/127(3%) were prescribed Versatis® compared to 26/129(20%) in 2017, all off-label.Indications included osteoarthritis and spinal stenosis. All four patients were prescribed the plaster prior to admission. Cost per plaster was €3.46 compared to €2.58 in 2017. Cost of Versatis® for these 4 admissions was €346 for their combined 100 bed days. Total cost of co-prescribed paracetamol for these four patients was €45.90. Three patients noted little analgesic benefit, one felt the plaster a psychological support. Seventeen different analgesics were prescribed across 127 kardexes. Conclusion: No patient was newly prescribed Versatis® during their admission. The MMP directive for the prescribing of Versatis® influenced prescribing practice across our hospital sites. Community practice for prescribing off-label is still evident for chronic pain, reflecting the difficulty of pain control in older adults. The cost of individual plasters increased by 0.88€ since 2017.